2009
DOI: 10.1158/1078-0432.ccr-08-2429
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of Eribulin Mesylate (E7389), a Mechanistically Novel Inhibitor of Microtubule Dynamics, in Patients with Advanced Solid Malignancies

Abstract: Purpose: Eribulin mesylate (E7389), a non-taxane microtubule dynamics inhibitor, is a structurally simplified, synthetic analogue of halichondrin B that acts via a mechanism distinct from conventional tubulin-targeted agents. This phase I study determined the maximum tolerated dose (MTD) and pharmacokinetics of eribulin administered on a 3 of 4 week schedule in patients with advanced solid malignancies. Experimental Design: Patients received eribulin mesylate (1-hour i.v. infusion) on days1, 8, and 15 of a 28-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
126
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(137 citation statements)
references
References 10 publications
10
126
1
Order By: Relevance
“…All 3 chemotherapeutic drugs have antineoplastic activity in various animal models (6,7,17) and human cancer conditions (2,37,38). Importantly, all 3 compounds have shown efficacy in multiple in vivo cancer efficacy models at doses often less than the MTD described in this study in the case of eribulin mesylate (17), or generally comparable with the MTD, in the case of paclitaxel (17) and ixabepilone (6,7).…”
Section: Discussionmentioning
confidence: 71%
“…All 3 chemotherapeutic drugs have antineoplastic activity in various animal models (6,7,17) and human cancer conditions (2,37,38). Importantly, all 3 compounds have shown efficacy in multiple in vivo cancer efficacy models at doses often less than the MTD described in this study in the case of eribulin mesylate (17), or generally comparable with the MTD, in the case of paclitaxel (17) and ixabepilone (6,7).…”
Section: Discussionmentioning
confidence: 71%
“…Several phase 1 studies of eribulin in patients with advanced solid tumors have demonstrated that eribulin has a manageable safety profile, with neutropenia and febrile neutropenia being the only dose-limiting toxicities observed [29] . (13079} [30] Two single-arm phase 2 studies evaluated eribulin monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…At the maximum tolerated dose (MTD), plasma levels of eribulin are above concentrations required for in vitro cytotoxicity for >1 week. Eribulin demonstrates a triphasic elimination with a halflife ranging from 36 to 48 hours (10)(11)(12), and it is eliminated primarily by biliary excretion. In a dedicated hepatic impairment trial, eribulin was generally safe and well tolerated.…”
Section: Pharmacokinetic Studiesmentioning
confidence: 99%
“…Hepatic dysfunction decreased clearance and prolonged elimination half-life, resulting in increased exposure to eribulin, when compared with patients with normal liver function (13). Renal excretion is minimal with 5% to 11% of the administered dose eliminated in the urine (10)(11)(12). CYP3A4 is the major enzyme responsible for eribulin metabolism; however, metabolism represents a minor component in drug clearance as no major human metabolites are formed.…”
Section: Pharmacokinetic Studiesmentioning
confidence: 99%